Facebook en el proceso de aprendizaje de los estudiantes de segundo de bachillerato de especialización aplicaciones informáticas de la Unidad Educativa Ismael Pérez Pazmiño de Machala 2013-2014. - Astudillo Gonzalez, Glenda Delfina (2016)
The way we communicate has changed drastically, social networks especially Facebook, have become a social phenomenon with billions of users worldwide, phenomenon in which students are immersed young people in particular. This research addresses the use of this web platform as a technological tool in the learning process, in the second year of specialty high school Computer Applications, parallel A B C section of the morning Ismael Pérez Pazmiño Education Unit of the city of Machala, El Oro province in the academic year 2013-2014. The theoretical foundation is based on the pedagogical models used in the PEA, methods and techniques for teaching and learning, teaching resources, educational software and multimedia technology. The purpose of the study is to determine the proper use of this web site can improve the teaching - learning. The research is descriptive literature and field type, the method is feasible project and interview techniques for teachers and student surveys, each with their respective instruments were used, the information displayed in tables and statistical graphs for better analysis and interpretation. With the results showed little use of social media by teachers as ICT, so it is proposed that a teacher refresher course Seminar - Workshop on applications for educational purposes of the social network Facebook with the purpose of granting the master new tools that motivate their actions and respond to the needs of students of this age.